A method for determining the content of trace impurity elements in bulk aluminum nitride

Through the DC glow discharge mass spectrometer combined with the acid solvent corrosion treatment method, the complex operation and pollution problems of the trace impurity element content determination in aluminum nitride are solved, and the accuracy of the detection results is improved.

CN113702485BActive Publication Date: 2025-04-11FIRST RARE MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111091904.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-17
Publication Date
2025-04-11
Estimated Expiration
2041-09-17

AI Technical Summary

Technical Problem

The prior art When determining the trace impurity element content in aluminum nitride, the operation is complicated and easy to introduce contamination, which reduces the accuracy of the detection results.

Method used

The DC glow discharge mass spectrometer was used to combine the acid solvent corrosion treatment. The corrosion-induced tantalum sheet was contacted with the corrosion-shaped bulk aluminum nitride sample to be tested, and the content of trace impurity elements was determined.

Benefits of technology

This method is simple to operate and does not easily introduce contamination. It can obtain strong and stable matrix signals, thereby improving the accuracy of the detection results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113702485B_ABST
    Figure CN113702485B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of analytical detection technology, and discloses a method for determining the content of trace impurity elements in bulk aluminum nitride. The method comprises: (1) first contacting a tantalum sheet with a first acidic solvent to obtain a corroded tantalum sheet; and second contacting a bulk aluminum nitride sample to be tested with a second acidic solvent to obtain a corroded bulk aluminum nitride sample to be tested; wherein, a through hole with a diameter of 1‑2 mm is provided on the tantalum sheet at intervals of 1‑2 mm; the first acidic solvent and the second acidic solvent are both a mixed solution of nitric acid and hydrofluoric acid in a volume ratio of 5‑10:1; the corroded tantalum sheet is placed on the corroded bulk aluminum nitride sample to be tested, and analyzed by a DC glow discharge mass spectrometer. The method provided by the present invention is simple to operate, not easy to introduce contamination, and can improve the accuracy of the detection results.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of analysis and detection, and in particular to a method for determining the content of trace impurity elements in bulk aluminum nitride. Background Art

[0002] As a third-generation semiconductor material, aluminum nitride has the characteristics of good thermal conductivity, high volume resistivity, small dielectric constant and dielectric loss, which makes it have broad application prospects in ultra-large-scale dust collection circuit substrates and packaging, high-power communication equipment, etc.

[0003] However, the purity of aluminum nitride, such as the content of certain metal elements (Mg, Fe, Si, etc.), will directly affect the performance of aluminum nitride. Therefore, how to effectively detect the impurities of aluminum nitride becomes crucial.

[0004] At present, the main methods for determining aluminum nitride impurities are flame atomic absorption spectrometry and plasma emission spectrometry. Both methods require sample digestion, and aluminum nitride has good high temperature resistance and corrosion resistance, which makes the digestion process complicated and easily introduces other impurities and reduces the accuracy of the test results.

[0005] Glow discharge mass spectrometer can directly analyze solid samples, avoiding the sample digestion process. It has high sensitivity and extremely wide linear dynamic range, and can determine impurity elements from ultra-trace to main content in one go. It has been widely used in ultra-pure solid materials.

[0006] CN109239179A discloses a method for determining impurity elements in high-purity aluminum oxide polycrystalline material, which is to press aluminum oxide polycrystalline particles onto a tantalum sheet and use a pulsed glow discharge mass spectrometer for determination. However, aluminum nitride has a high hardness and is difficult to adhere to the tantalum sheet, so this method is not suitable for the determination of non-conductive aluminum nitride.

[0007] Therefore, it is of great significance to develop a method that is simple to operate and has high accuracy to obtain the content of trace impurity elements in aluminum nitride. Summary of the invention

[0008] The purpose of the present invention is to solve the defects of the method for determining the content of trace impurity elements in aluminum nitride in the prior art, such as complex operation, easy introduction of pollution, and reduced accuracy of the detection result.

[0009] In order to achieve the above object, the present invention provides a method for determining the content of trace impurity elements in bulk aluminum nitride, the method comprising:

[0010] (1) contacting the tantalum sheet with a first acidic solvent to obtain a corroded tantalum sheet; and

[0011] The bulk aluminum nitride sample to be tested is brought into second contact with a second acidic solvent to obtain a corroded bulk aluminum nitride sample to be tested;

[0012] Wherein, the tantalum sheet is provided with through holes with a diameter of 1-2 mm at intervals of 1-2 mm;

[0013] The first acidic solvent and the second acidic solvent are both mixed solutions of nitric acid and hydrofluoric acid in a volume ratio of 5-10:1;

[0014] (3) placing the corroded tantalum sheet on the corroded bulk aluminum nitride sample to be tested, and analyzing the sample using a direct current glow discharge mass spectrometer;

[0015] The conditions of the DC glow discharge mass spectrometer include at least: a discharge current of 1.5-2 mA, a discharge voltage of 1000-1100 V, and a pre-sputtering time of 5-10 min.

[0016] The method provided by the present invention is simple to operate, is not prone to introducing contamination, and can obtain a strong matrix signal with good stability, thereby improving the accuracy of the detection result. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a schematic diagram of processing through holes on the tantalum sheet in Example 1;

[0018] Figure 2 is a schematic diagram of processing through holes on a tantalum sheet in Example 2;

[0019] Figure 3 This is a schematic diagram of through-hole processing on the tantalum sheet in comparative example 1;

[0020] Figure 4 This is a schematic diagram of through-hole processing on the tantalum sheet in comparative example 2;

[0021] Figure 5 are the current values ​​of Al at different times in Example 1 and Example 2. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] In the present invention, unless otherwise specified, the room temperature or normal temperature refers to 25±2°C.

[0024] As mentioned above, the first aspect of the present invention provides a method for determining the content of trace impurity elements in bulk aluminum nitride, the method comprising:

[0025] (1) contacting the tantalum sheet with a first acidic solvent to obtain a corroded tantalum sheet; and

[0026] The bulk aluminum nitride sample to be tested is brought into second contact with a second acidic solvent to obtain a corroded bulk aluminum nitride sample to be tested;

[0027] Wherein, the tantalum sheet is provided with through holes with a diameter of 1-2 mm at intervals of 1-2 mm;

[0028] The first acidic solvent and the second acidic solvent are both mixed solutions of nitric acid and hydrofluoric acid in a volume ratio of 5-10:1;

[0029] (4) placing the corroded tantalum sheet on the corroded bulk aluminum nitride sample to be tested, and analyzing the sample using a direct current glow discharge mass spectrometer;

[0030] The conditions of the DC glow discharge mass spectrometer include at least: a discharge current of 1.5-2 mA, a discharge voltage of 1000-1100 V, and a pre-sputtering time of 5-10 min.

[0031] It should be noted that the present invention has no special requirements on the type of the DC glow discharge mass spectrometer. It only needs to be able to analyze the content of trace impurity elements in the bulk aluminum nitride. Exemplarily, the DC glow discharge mass spectrometer of the present invention is an Astrum DC glow discharge mass spectrometer purchased from Nu Instruments.

[0032] It should be noted that in step (2), the tantalum sheet is placed on the bulk aluminum nitride sample to be corroded and mounted together on a sheet holder so that the bulk aluminum nitride sample to be corroded is exposed in the sputtering area.

[0033] Preferably, in step (1), the diameter of the through hole is 1 mm or 2 mm. The inventors have found that by adopting the specific implementation of this preferred case, a more stable and stronger matrix signal can be obtained.

[0034] Preferably, in step (1), the first acidic solvent and the second acidic solvent are both a mixed solution of nitric acid and hydrofluoric acid in a volume ratio of 8-10:1.

[0035] It should be noted that the present invention has no special requirements on the concentrations of the nitric acid and the hydrofluoric acid. By way of example, the concentration of the nitric acid in the present invention is 70-75wt%, and the concentration of the hydrofluoric acid is 45-50wt%.

[0036] Preferably, in step (1), the conditions for the first contact include at least: a temperature of 20-40° C. and a time of 2-5 min.

[0037] Preferably, in step (1), the conditions for the second contact include at least: a temperature of 20-40° C. and a time of 10-20 min.

[0038] Preferably, in step (1), the size of the tantalum sheet is (12-40)×(12-40)×(0.1-0.3) mm, and the purity of the tantalum sheet is not less than 99.99 wt%.

[0039] Preferably, in step (1), the size of the bulk aluminum nitride sample to be tested is (12-40)×(12-40)×(1-20) mm.

[0040] Preferably, in step (1), the method further comprises: performing a first washing and a first drying on the material obtained by the first contacting.

[0041] Preferably, in step (1), the method further comprises: performing a second washing and a second drying on the material obtained by the second contacting.

[0042] It should be noted that the present invention has no special requirements on the solvent, amount and number of solvents used in the first cleaning and the second cleaning, as long as the residual first acidic solvent or the second acidic solvent can be washed away. Exemplarily, the solvents used in the first cleaning and the second cleaning are both water, and the number of the first cleaning and the second cleaning is independently selected from 3-4 times.

[0043] It should be noted that the present invention has no special requirements on the operation methods of the first drying and the second drying. It is only necessary to air-dry the cleaned flat sheet or aluminum nitride sample.

[0044] Preferably, in step (2), the conditions of the DC glow discharge mass spectrometer include at least: a discharge current of 1.5-1.8 mA, a discharge voltage of 1000-1050 V, and a pre-sputtering time of 8-10 min.

[0045] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all the raw materials used are commercially available products.

[0046] The bulk aluminum nitride sample to be tested was purchased from Nu Instruments.

[0047] Tan film: purchased from Tongying Nonferrous Metals Company;

[0048] DC glow discharge mass spectrometer: model Astrum, purchased from Nu Instruments;

[0049] In the following examples, the analysis conditions of the DC glow discharge mass spectrometer are: discharge current is 1.5 mA, discharge voltage is 1050 V, and pre-sputtering time is 10 min;

[0050] In the following examples, the concentration of nitric acid is 71wt%, the concentration of hydrofluoric acid is 49wt%, and the concentration of ethanol is 99.7wt%;

[0051] In the following examples, the calculation formula of the relative standard deviation is: (standard deviation / average content)×100%.

[0052] Example 1

[0053] This embodiment provides a method for determining the content of trace impurity elements in bulk aluminum nitride, the method comprising:

[0054] (1) At room temperature, a processed tantalum sheet (size 15×15×0.2 mm, with 1 mm diameter holes opened every 1 mm, see Figure 1 ) using a first acidic solvent (a mixed solution of nitric acid and hydrofluoric acid in a volume ratio of 10:1) for etching for 2 minutes, then rinsing with pure water for 3 times, then washing with ethanol once and drying to obtain a corrosion flat sheet; and

[0055] At room temperature, a bulk aluminum nitride sample to be tested having a size of 20×20×1 mm was corroded with a second acidic solvent (a mixed solution of nitric acid and hydrofluoric acid in a volume ratio of 10:1) for 10 minutes, then rinsed with pure water for 3 times, and then washed with ethanol once and dried to obtain a corroded bulk aluminum nitride sample to be tested;

[0056] (2) Cover the bulk aluminum nitride sample with a thin tantalum sheet and mount them together on a sheet holder to ensure that the aluminum nitride is exposed in the sputtering area. Push the sample into the sample pool and analyze it using a DC glow discharge mass spectrometer. The specific test results are shown in Table 1.

[0057] Example 2

[0058] This embodiment provides a method for determining the content of trace impurity elements in bulk aluminum nitride, the method comprising:

[0059] (1) At room temperature, a processed tantalum sheet (size 15×15×0.2 mm, with through holes of 2 mm in diameter opened at 1 mm intervals, see Figure 2) using a first acidic solvent (a mixed solution of nitric acid and hydrofluoric acid in a volume ratio of 10:1) for etching for 3 minutes, then rinsing with pure water 4 times, then washing with ethanol once and drying to obtain a corroded tantalum sheet; and

[0060] At room temperature, an aluminum nitride having a size of 20×20×1 mm was corroded with a second acidic solvent (a mixed solution of nitric acid and hydrofluoric acid in a volume ratio of 10:1) for 20 minutes, then rinsed with pure water 4 times, washed once with ethanol and dried, to obtain a corroded high-purity aluminum nitride sample to be tested;

[0061] (2) Cover the bulk aluminum nitride sample with a thin tantalum sheet and mount them together on a sheet holder to ensure that the aluminum nitride is exposed in the sputtering area. Push the sample into the sample pool and analyze it using a DC glow discharge mass spectrometer. The specific test results are shown in Table 2.

[0062] Comparative Example 1

[0063] In this comparative example, the content of trace impurity elements in bulk aluminum nitride was determined according to the method of Example 1, except that in step (1), a through hole with a diameter of 3 mm was opened on the tantalum sheet (see Figure 3 ).

[0064] The remaining steps are the same as those in Example 1. The inventors found that the signal of the method in this comparative example is too low to be detected.

[0065] Comparative Example 2

[0066] In this comparative example, the content of trace impurity elements in bulk aluminum nitride was determined according to the method of Example 3, except that in step (1), a through hole with a diameter of 5 mm was opened on the tantalum sheet (see Figure 4 ).

[0067] The remaining steps are the same as those in Example 1. The inventors found that the signal of the method in this comparative example is too low to be detected.

[0068] Table 1: Test results of aluminum nitride samples in Example 1

[0069]

[0070] Table 2: Test results of aluminum nitride samples in Example 1

[0071]

[0072] It can be seen from Table 1 and Table 2 that when the method provided by the present invention is used to detect the content of trace elements in aluminum nitride, the sample surface contamination is small, and the relative standard deviation of the detection is within 10%, and the precision is good.

[0073] The present invention exemplarily provides the current values ​​of Al at different times in Example 1 and Example 2, see Figure 5 .

[0074] from Figure 5 It can be seen that when the method provided by the present invention is used for measurement, the current value of Al can reach 5E-11 and the signal is stable.

[0075] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for determining the content of trace impurity elements in bulk aluminum nitride, characterized in that: The method includes: (1) contacting the tantalum sheet with a first acidic solvent to obtain a corroded tantalum sheet; and The bulk aluminum nitride sample to be tested is brought into second contact with a second acidic solvent to obtain a corroded bulk aluminum nitride sample to be tested; Wherein, the tantalum sheet is provided with through holes with a diameter of 1-2 mm at intervals of 1 mm; The first acidic solvent and the second acidic solvent are both mixed solutions of nitric acid and hydrofluoric acid in a volume ratio of 5-10:1; (2) placing the corroded tantalum sheet on the corroded bulk aluminum nitride sample to be tested, and analyzing the sample using a direct current glow discharge mass spectrometer; The conditions of the DC glow discharge mass spectrometer include at least: a discharge current of 1.5-2 mA, a discharge voltage of 1000-1100 V, and a pre-sputtering time of 5-10 min.

2. The method according to claim 1, wherein: In step (1), the diameter of the through hole is 1 mm or 2 mm.

3. The method according to any one of claims 1 or 2, wherein: In step (1), the first acidic solvent and the second acidic solvent are both a mixed solution of nitric acid and hydrofluoric acid in a volume ratio of 8-10:

1.

4. The method according to any one of claims 1 or 2, wherein: In step (1), the conditions of the first contact include at least: a temperature of 20-40° C. and a time of 2-5 min.

5. The method according to any one of claims 1 or 2, wherein: In step (1), the conditions for the second contact include at least: a temperature of 20-40° C. and a time of 10-20 min.

6. The method according to any one of claims 1 or 2, wherein: In step (1), the size of the tantalum sheet is (12-40)×(12-40)×(0.1-0.3) mm, and the purity of the tantalum sheet is not less than 99.99 wt%.

7. The method according to any one of claims 1 or 2, wherein: In step (1), the size of the bulk aluminum nitride sample to be tested is (12-40)×(12-40)×(1-20) mm.

8. The method according to any one of claims 1 or 2, wherein: In step (1), the method further comprises: performing a first cleaning and a first drying on the material obtained by the first contact.

9. The method according to any one of claims 1 or 2, wherein: In step (1), the method further comprises: performing a second washing and a second drying on the material obtained by the second contacting.

10. The method according to any one of claims 1 or 2, wherein: In step (2), the conditions of the DC glow discharge mass spectrometer include at least: a discharge current of 1.5-1.8 mA, a discharge voltage of 1000-1050 V, and a pre-sputtering time of 8-10 min.

Citation Information

Patent Citations

  • Method for determining trace impurity elements in high purity alumina polycrystalline material

    CN109239179A

  • Method for detecting contents of impurity elements in aluminum hydroxide via glow discharge mass spectrometry

    CN110186997A

  • Glow discharge spectrometer

    US4912324A